2017
DOI: 10.1186/s12879-017-2621-4
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic hyperthermia enhance the treatment efficacy of peri-implant osteomyelitis

Abstract: BackgroundWhen bacteria colony persist within a biofilm, suitable drugs are not yet available for the eradication of biofilm-producing bacteria. The aim of this study is to study the effect of magnetic nano-particles-induced hyperthermia on destroying biofilm and promoting bactericidal effects of antibiotics in the treatment of osteomyelitis.MethodsSixty 12-weeks-old male Wistar rats were used. A metallic 18G needle was implanted into the bone marrow cavity of distal femur after the injection of Methicillin-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 48 publications
1
52
0
Order By: Relevance
“…Chopra et al have shown, in a mouse model, that thermal damage is confined to a localized region (< 2 mm) around the implant [8]. Fang et al heated metal implants in a rat model to 75 C without any significant thermal damage to the surrounding tissue [31]. These studies are in agreement with Samara et al, who have shown that bone cement achieves durable fixation despite the temperature reaching 80 C for more than 10 min, caused by the curing process of the cement [14].…”
Section: Discussionmentioning
confidence: 99%
“…Chopra et al have shown, in a mouse model, that thermal damage is confined to a localized region (< 2 mm) around the implant [8]. Fang et al heated metal implants in a rat model to 75 C without any significant thermal damage to the surrounding tissue [31]. These studies are in agreement with Samara et al, who have shown that bone cement achieves durable fixation despite the temperature reaching 80 C for more than 10 min, caused by the curing process of the cement [14].…”
Section: Discussionmentioning
confidence: 99%
“…The intramuscular route showed a similar tendency to suppress S. aureus accumulation in bone. Osteomyelitis was also treated by magnetic Fe 3 O 4 nanoparticles with the induction of hyperthermia to disrupt biofilm (Fang et al, 2017). The SPIONs were implanted in bone infected by S. aureus.…”
Section: The Other Infection Sitesmentioning
confidence: 99%
“…An in vivo study investigated the use of magnetic particles hyperthermia to destroy biofilms generated in peri-implant osteomyelitis [58]. A metallic needle was implanted into the bone marrow cavity of rats and heated to 75 for up to 30 s at a time using an alternated magnetic field.…”
Section: Thermal Therapy As An Adjuvant Modality For the Treatment Ofmentioning
confidence: 99%